"Preorder-online, pickup-in-store" strategy for a dual-channel retailer. (February 2019) - Zhang, Peng; He, Yong; Zhao, Xuan
Highlights: We study "preorder-online, pickup-in-store" (POPU) for a dual-channel retailer. Under the monopoly case, the retailer cannot benefit from POPU. Under competition, POPU is beneficial for retailer under certain conditions. Abstract: This paper studies the "preorder-online, pickup-in-store" (POPU) strategy for a dual-channel retailer. Under a monopoly case, we find that the POPU strategy decreases the retailer's market share and reduces his profits. Under a competition case, when the operational cost of POPU mode is low, the POPU strategy can improve the retailer's market share and profits simultaneously. Also, we find that not all products are suited for the POPU mode under a competition case. The retailer should choose products with high value and a low degree of customer acceptance of the online channel for POPU.